Development of Literation Learning Devices Science Based on Local Wisdom - Syahidan Nurdin; Nurul Ainanur; Misbahul Jannah (Jurnal Pendidikan Profesi Guru, 2023)
Lack of learning resources is a problem found at SDN Panton New Area of South Aceh. This makes Literature a curriculum, especially literacy science based on local wisdom in the learning process is important to develop. This research aims to design device learning scientific literacy based on local wisdom and testing feasibility a scientific literacy learning tool based on local wisdom in South Aceh. This research method is research and development that refers on 4D models that is Define (Definition), Design (Design), Develop (Development), Disseminate (Spread). Research result show that the feasibility of science-based literacy learning devices South Aceh's local wisdom was assessed by the media validator obtaining 87.5% in the "Very Eligible" category, the results of the material validation obtained feasibility achieved 91.16% with the category "Very Eligible", and language validation results obtained 85.25% in the "Very Eligible" category. Thus can it was concluded that the learning device products developed were feasible to use in the process learning.